Efficacy of probiotic, prebiotic, and synbiotics supplements in individuals with anemia: a systematic review and meta-analysis of randomized controlled trials - Qian Hu; Ying Liu; Youmei Fei; Jingping Zhang; Shao Yin; Hui Zou; Fengya Zhu (BMC Gastroenterology)
Abstract Introduction Anemia is a common global health problem, particularly in impoverished regions, with a high incidence rate. The condition is multifactorial, with iron deficiency being one of the most prevalent causes. Current treatment for anemia often relies on iron supplements or erythropoiesis-stimulating agents, although these therapies may show limited efficacy for some patients. Recent evidence suggests that probiotics, prebiotics, and synbiotics, as microbiome modulators, hold significant potential in the treatment of anemia. These interventions may enhance iron absorption and improve overall blood health through their impact on gut microbiota, thus providing an alternative or complementary approach to conventional treatments. Methods Six databases, including the Cochrane Central Register of Controlled Trials, Embase, PubMed, Web of Science (WOS), China National Knowledge Infrastructure (CNKI), and WangFang data library, were searched up to November 20, 2024. Studies published in English and Chinese were included. We included randomized controlled trials (RCTs) evaluating the effects of probiotics, prebiotics, or synbiotics in treating anemia. The experimental groups received probiotics, prebiotics, or synbiotics, while the control groups received placebo, alternative treatments, or no treatment. The primary outcome was hemoglobin (Hb) levels. Secondary outcomes included serum iron (SI) and serum ferritin (SF). A descriptive analysis was conducted for studies where meta-analysis was not feasible. The GRADE tool was used to assess the quality of evidence, and the Cochrane guidelines were employed to evaluate the risk of bias in each study. Results Seven studies were included comprising a total of eight RCTs, with the main types of anemia being iron deficiency anemia (IDA) and anemia of chronic kidney disease (CKD), involving 632 patients. The analysis revealed that probiotics, prebiotics, or synbiotics significantly improved Hb levels in patients with anemia (WMD = 10.760, 95% CI: 4.593 to 16.747, p = 0.001), though heterogeneity was high (I² = 96.5%). Two RCTs (n = 120 participants) reported significant increases in serum iron levels in the probiotic group (WMD = 3.835, 95% CI: 3.271 to 4.400), with moderate heterogeneity (I² = 38.7%). Two RCTs (n = 192 participants) reported no significant differences were observed between the groups in serum ferritin levels (WMD = 8.048, p = 0.115), and heterogeneity remained high (I² = 62.6%). Subgroup analyses revealed that probiotics improved Hb levels in renal and iron-deficiency anemia, as well as across different doses. The synbiotic group showed consistent efficacy (I² = 0%), while the prebiotic group did not exhibit significant effects, with extremely high heterogeneity (I² = 99.3%). This indicates that heterogeneity may stem from variations in intervention types, and the results should be interpreted with caution. Conclusion There is moderate-quality evidence suggesting that probiotics, prebiotics, and synbiotics may improve anemia management, particularly by enhancing Hb levels. Further high-quality RCTs are required to explore the specific role of synbiotics in anemia management, including their comparative efficacy against probiotics and prebiotics alone, and their impact on gastrointestinal factors such as gut microbiota modulation and inflammation reduction. Systematic review registration PROSPERO CRD42024590073.